Detection Candida albicans In The Urine Of Women With Diabetes Mellitus Using The PCR Method - Elfira Dwi Novi Nastiti; Muhammad Taufiq Qurrohman (LPPM Universitas Abdurrab, 2025)
Candida albicans is a fungus that has dimorphic abilities that can grow in the form of yeast or hyphae. Candida albicans fungus can be found in various parts of the human body, including the urinary tract. In individuals with Diabetes Mellitus, high blood glucose levels can increase the risk of fungal infections, because glucose in the urine provides an environment that supports fungal growth. Candida albicans fungus can be detected molecularly which aims to identify DNA in the fungus and the initial molecular stage carried out is DNA isolation. The purpose of this study was to determine the presence or absence of Candida albicans fungus in urine isolate samples of women with diabetes mellitus at the Pajang Health Center, Surakarta City. The research method used was descriptive using a cross-sectional approach. The samples used were urine samples of women with diabetes mellitus at the Pajang Health Center, Surakarta City. Based on the results of the study, data analysis and discussion in this study, it can be concluded that Candida albicans fungus can be detected in the ITS1 region at 219 bp and ITS2 at 338 bp using the Polymerase Chain Reaction (PCR) method.